(untitled) (Revista de Ciências Agroveterinárias, 2016)
In Brazil today there are large areas of grassland in some stage of degradation due to inadequate handling, particularly with regard to lack of use of phosphate fertilizer. This study aimed to evaluate the productivity and bromatologic composition of three species of tropical forages under the residual effect of phosphorus fertilization. The randomized block design was applied in a 3x5x2 factorial scheme with three forages (Panicum maximum cvs. Tanzania and Mombaça and Brachiaria sp. cv. Mulato), five P rates (0, 40, 80, 120 and 240 kg ha-1), and two cuts (October and November of 2007) with three replicates. The deployment of pasture was held in September 2005, and the area remained under constant grazing and management, with regular cleaning and mowing for two years. In October and November of 2007, the following parameters were evaluated - fresh matter yield (FM), dry matter yield (DM) and contents of crude protein (CP), neutral detergent fiber (NDF), acid detergent fiber (ADF), hemicellulose (HEM) and mineral matter (MM). Phosphorus fertilization until the maximum dose of 240 kg ha-1 did not promote residual effect on yield and chemical composition of Tanzania, Mombaça and Mulato grasses after two years of application in oxisol, with P fertilizer higher than 4.2 mg dm3, whose averages for the accumulation of DM and CP, NDF and ADF were 9.7 Mg ha-1, 11.8%, 77.8% and 41.3%, respectively.